Nahdlatul Ulama (NU) in Central Sumatra During the PRRI Period (1958-1961) - Muhammad Yunus; Zulqayyim Zulqayyim; Yusmarni Djalius (Regalia Institute, 2025)
This study aims to analyze the development of Nahdlatul Ulama (NU) in Central Sumatra and the organization’s political stance in responding to the Revolutionary Government of the Republic of Indonesia (PRRI) conflict in the late 1950s. It also seeks to explain the dynamics of NU’s relationship with regional political elites and the central government, as well as the impact of the PRRI conflict on the development of NU in West Sumatra. This research employs the historical method, consisting of four main stages: heuristics, source criticism, interpretation, and historiography. The findings indicate that Nahdlatul Ulama (NU) began to develop organizationally in Central Sumatra in the early 1950s through the efforts of several prominent figures, some of whom originated from the Persatuan Tarbiyah Islamiyah (Perti) milieu. Although NU secured only limited electoral support in the 1955 General Election, the organization remained actively involved in regional political affairs. During the initial phase of the PRRI conflict, NU supported the Dewan Banteng; however, it subsequently aligned itself with the central government's policy when the conflict evolved into an armed rebellion against Jakarta. Following the end of the PRRI conflict, administrative restructuring and organizational reorganization contributed to the strengthening of NU at the regional level. During the Guided Democracy period, NU experienced significant growth through the expansion of its organizational network, an increase in membership, and greater participation in political institutions. These developments demonstrate the close relationship between the evolution of religious organizations and broader political transformations at both the regional and national levels.